2015
DOI: 10.1016/j.elspec.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Principle and application of low energy inverse photoemission spectroscopy: A new method for measuring unoccupied states of organic semiconductors

Abstract: Information about the unoccupied states is crucial to both fundamental and applied physics of organic semiconductors. However, there were no available experimental methods that meet the requirement of such research. In this review, we describe a new experimental method to examine the unoccupied states, called low-energy inverse photoemission spectroscopy (LEIPS). An electron having the kinetic energy lower than the damage threshold of organic molecules is introduced to a sample film, and an emitted photon in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 72 publications
2
70
0
1
Order By: Relevance
“…Inverse photoemission spectroscopy has been used for this purpose, although the high‐energy electron beam can damage organic materials, preventing accurate evaluation of the EA. Recently, Yoshida developed low‐energy inverse photoemission spectroscopy (LEIPS), which can be used to measure the EA of organic semiconductors more accurately . LEIPS prevents damage by reducing the beam energy to less than 5 eV, which leads to high sensitivity measurements because emission in the near‐UV region is detected.…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…Inverse photoemission spectroscopy has been used for this purpose, although the high‐energy electron beam can damage organic materials, preventing accurate evaluation of the EA. Recently, Yoshida developed low‐energy inverse photoemission spectroscopy (LEIPS), which can be used to measure the EA of organic semiconductors more accurately . LEIPS prevents damage by reducing the beam energy to less than 5 eV, which leads to high sensitivity measurements because emission in the near‐UV region is detected.…”
Section: Preparation and Characterization Of Planar Heterojunctionsmentioning
confidence: 99%
“…Recently, we have developed an experimental method called low-energy inverse photoemission spectroscopy (LEIPS) [24] which is an advanced version of the inverse photoemission spectroscopy (IPES). We have so far determined A s of several organic materials with a precision of 0.1 eV [24][25][26][27][28][29][30][31][32]. Further, we have demonstrated that the precisely determined A s as well as I s allows us to distinguish the contribution of the polarization energy to the energy level change induced by the thermal crystallization of organic film of [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) [33].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In this technique, electrons having a kinetic energy below 5 eV are introduced to the sample surface, and photons emitted due to the radiative transition to the unoccupied states are detected.…”
Section: Introductionmentioning
confidence: 99%